Terra Preta production from Ghanaian and Zambian soils using domestic wastes - Neina, Dora; Glaser, Bruno (Scientific reports, 2024)
Quests for productive soils to close yield gaps call for innovative strategies. This study tested an off-site formation of the Amazonian Terra Preta (TP) in a potential modern analogon under coastal savannah climatic conditions of Ghana. Four Ghanaian and two Zambian soils; two types of biochar (i.e., rice husk biochar and charcoal residues); domestic wastes (i.e., kitchen leftovers, animal manures, human urine, and kitchen ash) were mixed with the soils wetted to 100% water holding capacity, and incubated under aerobic conditions for nine months. Indicators of the TP include total carbon (C), pH, base saturation, basic cations, and plant-available P, which were measured using standard methods of soil analysis. The TP formation enhanced soil pH by 0.02 to 2.9, ranging from pH 7.2 to 8.2, with charcoal residues having the highest effect on pH. The modern TP was characterized by relatively high total C, pH, K, Ca, Mg, Na, base saturation, and plant-available P. These properties reflect unique interactions between the chars, wastes, and soils, suggesting the potential for on-site TP formation. It calls for further studies, commitment, and perseverance in their formation in the future.